2010
DOI: 10.4137/nmi.s4460
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nutritional Supplements on Immune Function and Body Weight in Malnourished Adults

Abstract: In the United States, approximately 5% of the population is malnourished or has low body weight, which can adversely affect immune function. Malnutrition is more prevalent in older adults and is often a result of energy imbalance from various causes. Dietary supplementation to promote positive energy balance can reverse malnutrition, but has not been assessed for its effect on immune parameters. This 8-week clinical feeding trial evaluated the effect of a commercially available, high-protein, high-energy formu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…NUTRITION AND LIFESTYLE appetite and weight loss are major issues [46]. In the United States, approximately 5% of the population either is malnourished or has low body weight [48]. Isaac et al [46], using a sample of 242 adults drawn from the Nutrition for Health Living (NFHL) study-an observational cohort study in adults with HIV -found that well over a third (37%) of their subjects with depression had a lower total energy intake and more decreases in their overall dietary components compared with their counterparts without depression.…”
Section: Self-regulation Skills-abilities: Depressionmentioning
confidence: 99%
“…NUTRITION AND LIFESTYLE appetite and weight loss are major issues [46]. In the United States, approximately 5% of the population either is malnourished or has low body weight [48]. Isaac et al [46], using a sample of 242 adults drawn from the Nutrition for Health Living (NFHL) study-an observational cohort study in adults with HIV -found that well over a third (37%) of their subjects with depression had a lower total energy intake and more decreases in their overall dietary components compared with their counterparts without depression.…”
Section: Self-regulation Skills-abilities: Depressionmentioning
confidence: 99%
“…The effects of nutritional interventions on immune function and other parameters (especially body weight) in malnourished adults has also been evaluated in many studies [ 82 , 83 ]. However, the differences in the physiology and metabolism between children and adults must be noted and taken into account in the extrapolation of the results or for the understanding of the underlying mechanisms of how specific nutrients affect the immune systems in target populations.…”
Section: Gaps and Perspectivesmentioning
confidence: 99%
“…Malnutrition is more prevalent among older adults, but this can be reduced by providing a positive energy balance for both total calories and protein [82]. A target of 25-30 g of protein per meal should be achieved at multiple feeding occasions to promote muscle protein synthesis in the elderly, and it cannot be ignored that protein supplementation affects the appetite and energy intake of middle-older aged adults [83].…”
Section: Protein Enrichmentmentioning
confidence: 99%